Analisis Penerapan Program Tax Amnesty Di Indonesia - Sayoga, Valdi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to analyze the application of the Tax Amnesty Program and the results generated by the Program to the Level of Taxpayer Compliance, Tax Management, and its Contribution to the Establishment of the Taxation System. The type of research conducted is descriptive qualitative research by collecting materials from the literature, website research and then discussing the Tax Amnesty event based on materials taken from the literature. The results of this study indicate that the Tax Amnesty Program is able to increase Taxpayer Risk Levels, provide taxpayers with ease in their tax matters, but the Tax Amnesty Program does not have a stake in tax management from taxpayers. It is also found that the Tax Amnesty Program has several weaknesses that have been anticipated by other Government Regulations.